Modern View on the Etiology and Methods of Treatment of Bruxism: а Review - Elena V. Terentyeva; Olga Yurova; Anastasia D. Dubinskaya (Вестник восстановительной медицины)
INTRODUCTION. Currently, the prevalence of bruxism ranges from 9 % to 32 % of the total population, of which 6 % to 20 % are adults, while the question of the etiology of bruxism remains open, due to the presence of various theories of the development of this disease.